2019
DOI: 10.1002/mp.13962
|View full text |Cite
|
Sign up to set email alerts
|

Lateral head flexion as a noncoplanar solution for ring gantry stereotactic radiosurgery

Abstract: Purpose Ring gantry radiotherapy devices are often limited to deliver beams in the axial plane, severely limiting beam entrance angles and rendering noncoplanar beam delivery impossible. However, a ring gantry geometry greatly simplifies delivery machines and increases the efficiency of treatment with the potential to decrease the overall costs of radiotherapy. This study explores the use of lateral head flexion in order to increase beam entrance angles and extend the available solid angle space for a ring gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It thus improves plan conformity and normal tissue sparing. Reynoso et al [39] did the research and found that when comparing the head flexion technique with a fully coplanar geometry, the Halcyon SRS plans showed an average improvement in CI of 7.3% (1.46 ± 0.25 vs 1.36 ± 0.28), a decrease of 13% in intermediate dose fall-off (5.46 ± 1.14 vs 4.78 ± 1.12), a decrease of 32% in low dose spillage (85.7 ± 20.3 vs 58.2 ± 15.1), and a decrease of 7.8% in gradient measure (0.53 ± 0.05 vs 0.49 ± 0.04). Li et al [40] conducted a retrospective study of ten patients with multiple intracranial metastases, each with 6 to 10 targets with a volume of 0.11 to 8.57 cc and a prescribed dose of 15 to 24 Gy.…”
Section: Resultsmentioning
confidence: 99%
“…It thus improves plan conformity and normal tissue sparing. Reynoso et al [39] did the research and found that when comparing the head flexion technique with a fully coplanar geometry, the Halcyon SRS plans showed an average improvement in CI of 7.3% (1.46 ± 0.25 vs 1.36 ± 0.28), a decrease of 13% in intermediate dose fall-off (5.46 ± 1.14 vs 4.78 ± 1.12), a decrease of 32% in low dose spillage (85.7 ± 20.3 vs 58.2 ± 15.1), and a decrease of 7.8% in gradient measure (0.53 ± 0.05 vs 0.49 ± 0.04). Li et al [40] conducted a retrospective study of ten patients with multiple intracranial metastases, each with 6 to 10 targets with a volume of 0.11 to 8.57 cc and a prescribed dose of 15 to 24 Gy.…”
Section: Resultsmentioning
confidence: 99%